2004
DOI: 10.1074/jbc.m403335200
|View full text |Cite
|
Sign up to set email alerts
|

The Cytoplasmic Tyrosine Kinase Pyk2 as a Novel Effector of Fibroblast Growth Factor Receptor 3 Activation

Abstract: Activating mutations within fibroblast growth factor receptor 3 (FGFR3), a receptor tyrosine kinase, are responsible for human skeletal dysplasias including achondroplasia and the neonatal lethal syndromes thanatophoric dysplasia types I and II. Several of these same FGFR3 mutations have also been identified somatically in human cancers, including multiple myeloma, bladder carcinoma, and cervical cancer. The molecular pathways exploited by FGFR3 to stimulate abnormal proliferation during neoplasia are unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 57 publications
(69 reference statements)
2
18
1
Order By: Relevance
“…This residue seems important in internalisation process as demonstrated by studying truncated receptors lacking Tyr-1173 and Tyr-1212. 61 This process occurs in ECs growing on native ECM, as demonstrated by the data showing that this phosphatase is also activated by VEGF-A 165 in ECs adherent to this ECM (Figures 2A, 2B, and 3) as well as in cells on collagen I. Here, we did not address the behavior of the internalized VEGFR-2 in EC adhering on collagen I. VEGFR-2 could either be accumulated in the endosomal compartment and degraded or recycled to the membrane, thus allowing a different degree of EC activation or a modified spatial regulation of the signal.…”
Section: Discussionmentioning
confidence: 99%
“…This residue seems important in internalisation process as demonstrated by studying truncated receptors lacking Tyr-1173 and Tyr-1212. 61 This process occurs in ECs growing on native ECM, as demonstrated by the data showing that this phosphatase is also activated by VEGF-A 165 in ECs adherent to this ECM (Figures 2A, 2B, and 3) as well as in cells on collagen I. Here, we did not address the behavior of the internalized VEGFR-2 in EC adhering on collagen I. VEGFR-2 could either be accumulated in the endosomal compartment and degraded or recycled to the membrane, thus allowing a different degree of EC activation or a modified spatial regulation of the signal.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that the FGFR3 juxtamembrane domain interacts with Pyk2, a focal adhesion kinase, whose activity is required for STAT5 phophorylation. However, FGFR3 (TDII) can override the requirement of Pyk2 for the activation of STAT5 [136]. STAT5, which is known to induce cyclin D1 expression, has been shown to be involved in cell proliferation and may represent a good candidate for downstream signalling in FGFR3-positive cancers [137].…”
Section: Fgfr3 Signalling and Transcriptional Consequencesmentioning
confidence: 99%
“…Since the cytoplasmic tyrosine kinase Pyk2 has been recently indicated as a novel effector of FGFR3 activation, 27 we investigated whether Pyk2 could play any role in the signaling pathway triggered by the SADDAN and TDII mutants. For this purpose, cell lysates from transiently transfected HEK293 cells were compared with cell lysates from the stable cell lines.…”
Section: Fgfr3 Derivatives Recruit Pyk2 From the Ermentioning
confidence: 99%